Ø§Ù„Ù‚ÙŠÙ… Ø§Ù„Ø£Ø®Ù„Ø§Ù‚ÙŠØ© ÙÙŠ Ø³ÙˆØ±Ø© Ø§Ù„Ø¥Ø³Ø±Ø§Ø¡ ÙˆØªÙ†Ù…ÙŠØªÙ‡Ø§ Ù„Ù„Ø£Ø·ÙØ§Ù„ ÙˆØ§Ù„Ø¨Ø§Ù„ØºÙŠÙ† - Fauziyah, Nur Laily (Almarhalah | Jurnal Pendidikan Islam, 2018)
The good character decorates human. It makes him loved in society and is one of the reasons for the happiness of man in this life and to enter Paradise in the Hereafter. Bad manners cause human agony and entering the fire in the Hereafter. As we have seen in the time of now many people sabotage their manners. The development of moral values of children and raising them is very important, by mentioning that children and youth struggled to their country. The purpose of a scientific and in-depth study of this research, including knowing the Islamic moral values emanating in Al-Isra and means any way to develop for children and adults. The moral values emerging from the verses in Surat Al-Israa include moral values when treating people with the Creator, ethical values when treating people with parents, ethical values when treating people with society and individual moral values.